2005
DOI: 10.1001/archinte.165.16.1882
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotics and Parkinsonism

Abstract: The risk of development of parkinsonism associated with the use of high-dose atypical antipsychotics was similar to that associated with the use of typical antipsychotics. Caution should be used when prescribing atypical antipsychotic therapy at high doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(114 citation statements)
references
References 17 publications
(16 reference statements)
7
103
0
3
Order By: Relevance
“…A 30-year population-based study indicated that DIP is the fifth most common cause of Parkinsonism [21]. Several previous studies have investigated DIP caused by antipsychotics [21,22], calcium channel blockers [17], and antiemetics [23]. Although DIP has been reported in patients treated with TMZ [10,11], little is known about the risk of Parkinsonism induced by TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…A 30-year population-based study indicated that DIP is the fifth most common cause of Parkinsonism [21]. Several previous studies have investigated DIP caused by antipsychotics [21,22], calcium channel blockers [17], and antiemetics [23]. Although DIP has been reported in patients treated with TMZ [10,11], little is known about the risk of Parkinsonism induced by TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…Acute care hospital admissions were divided into 2 categories: known serious events (ie, EPS, falls or hip fractures, and cerebrovascular events) or other events. The EPS, including parkinsonism 3 and other druginduced movement disorders, 2 as well as falls 4 20 We defined other hospital admissions as acute care hospital admissions that were not for one of these known events.…”
Section: Data Management: Definitions and Standards For Expedited Repmentioning
confidence: 99%
“…While Health Canada warnings for increased rates of cerebrovascular adverse events and mortality based on the RCTs of the atypical antipsychotics had already been published at the time of the third CCCDTD and were carefully considered, subsequent RCTs and data from large administrative health databases raise further concerns about the safety of the antipsychotics in older dementia patients. Th ese concerns include cognitive decline [89], adverse metabolic eff ects [90,91], and extrapyramidal symptoms [92]. Similarly, newer studies appear to confi rm the risk of excess mortality in antipsychotic-treated patients with dementia, although diff erent antipsychotics may have relatively diff erent risks and some other nonantipsychotic drugs may carry similar risks [93][94][95][96].…”
Section: Rationalementioning
confidence: 99%